EFEKTIFITAS AIR KELAPA MUDA DAN BIOURIN SEBAGAI ZAT PENGATUR TUMBUH TERHADAP VIABILITAS BENIH INDIGOFERA (Indigofera ollingeriana) PADA MEDIA TANAM YANG BERBEDA - Ali, Najmah; Dahniar, Dahniar (Agros Journal of Agriculture Science, 2024)
Indigofera (Indigofera zollingeriana) is a tree legume type of forage that has good nutritional content for ruminants and can be harvested periodically without having to replant it. The aim of the research was to see the effectiveness of soaking seeds in young coconut water and biourine in the planting medium of compost, cocopeat and a combination of compost + cocopeat on the ability to germinate, number of leaves and height of indigofera plants (Indigofera zollingeriana). The materials used are certified indigofera seeds from the Jonggol Livestock Research and Education Unit, Bogor Agricultural Institute, young coconut water, compost, biourine, cocopeat and water. This research used a Completely Randomized Factorial Design. Factor A is coconut water and biourine, factor B is compost, cocopeat and compost+cocopeat planting media. The parameters observed were germination percentage, number of leaves and plant height. The results showed that soaking seeds with young coconut water and biourine had an effect on germination. Compost, cocopeat and compost + cocopeat planting media have an effect on plant height. There is an interaction between soaking seeds using young coconut water and biourine in compost, cocopeat, compost+cocopeat planting media on the percentage of seed germination. Keywords:  coconut water, goat biourine, cocopeat, viability, germination. INTISARIIndigofera (Indigofera zollingeriana) adalah merupakan  hijauan pakan ternak berjenis leguminosa pohon yang memiliki kandungan nutrisi yang cukup baik untuk ternak ruminansia dan dapat dipanen secara berkala tanpa harus menanamnya kembali.   Tujuan penelitian adalah untuk melihat efektifitas perendaman benih dengan air kelapa muda dan biourin  pada  media tanam kompos, cocopeat dan kombinasi kompos + cocopeat terhadap kemampuan berkecambah, jumlah daun dan tinggi tanaman indigofera (Indigofera zollingeriana). Materi yang digunakan adalah  benih indigofera tersertifikasi dari Unit Penelitian dan Pendidikan Peternakan Jonggol Institut Pertanian Bogor, air kelapa muda, kompos, biourin, cocopeat dan air.  Penelitian ini menggunakan Rancangan Acak Lengkap Pola Faktorial. Faktor A adalah air kelapa dan biourin, faktor B adalah media tanam kompos, cocopeat dan kompos+cocopeat.  Parameter yang diamati adalah persentase perkecambahan, jumlah daun dan tinggi tanaman.  Hasil penelitian menunjukkan bahwa perendaman benih dengan air kelapa muda dan biourin berpengaruh terhadap perkecambahan. Media tanam kompos, cocopeat dan kompos + cocopeat  berpengaruh terhadap tinggi tanaman. Terdapat interaksi antara perendaman benih menggunakan air kelapa muda dan biourin  pada media tanam kompos, cocopeat,  kompos+cocopeat  terhadap persentase perkecambahan benih.  Kata-kata kunci: air kelapa muda, biourin kambing, cocopeat, viabilitas dan perkecambahan.